Ministerial Education Councils’ Capacity for Policy Decision-Making in Canada, Germany, and Switzerland: Finding a Balanced Perspective - Faubert, Brenton (International Journal of Education Policy and Leadership, 2021)
Scholars have become increasingly vigilant about leaders, the role of government and wider governance bodies, and their influence on education policy. Councils in Europe and North America, generally, and education councils, specifically, are good examples of influential bodies whose decision-making processes have rightfully come under scrutiny; however, many scholarly assessments have been characterized by rhetorical claims that focus on these bodies’ limited ability to make decisions and address social challenges. This article details a qualitative, comparative case study conducted in 2018 that investigated how Councils of Ministers of Education in Canada, Germany, and Switzerland address national educational issues of collective interest. The resulting dataset is comprehensive, and this research invites colleagues to refine or rethink some of their limiting rhetorical tools and underlying assumptions.